A Model for Opinion Ranking - Lima, Allan D. S.; Sichman, Jaime S. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2012)
Day after day we have been noticing the growth in the number of opinions about any subject over the Internet. Consequently it’s becoming hard for people to know what others think about a subject. In order to proper han dle this problem, a research field called opinion mining was created. One of its objectives is to classify the relevance of an opinion. Focusing in this point, we present in this paper a model to rank opinions. Our model is based in the composition of a ranking function by combining many concepts. Some of them are related to social aspects of the user who is searching for opinions. Also we discuss how to find the best combination of our parameters and how our mod el is different for projects where opinions were ranked before.